Rancang Bangun Sistem Kendali Otomatis Draining di Continuous Settling Tank - Ahmad Mahfud (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
The design of automatic equipment draining using a solenoid valve and time delay relay is a innovation at the Palm Oil Mill (POM) regarding the draining work that exists in POM. Draining is the disposal of the resulting material from sediment formed from the deposition process at the clarification station, which is a routine work that must be done, but most operators do not routinely do it, because generally it is still done manually in the POM in Indonesia. Non-routine sand removal will cause several problems, ie sand is abrasive to equipment/machinery, decreases processing efficiency, and reduces processing capacity because the process space is filled with sand. So from that the design is made based on the problem, where the drain drain can be done automatically with the use of a solenoid valve, and the discharge time can be set using time delay relay. Based on the results of the research conducted, the adjustment times for Timer 1, 2 and 3 are obtained, namely 177 seconds, 10 seconds and 88 seconds. The total time will be wasted as much as 1,570 cm3 of water which is in the tool building.